2017
DOI: 10.3747/pdi.2016.00201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of A 12-Month Pilot of Long-Term and Temporary Assisted Peritoneal Dialysis

Abstract: ♦ BACKGROUND: Peritoneal dialysis (PD) is challenging for patients with functional limitations, and assisted PD can support these patients, but previous reports of assisted PD have not examined the role of temporary assisted PD and had difficulty identifying adequate comparator cohorts. ♦ METHODS: Peritoneal Dialysis Assist (PDA), a 12-month pilot of long-term and temporary assisted PD was completed in multiple PD centers in British Columbia, Canada. Continuous cycler PD (CCPD) patients were identified for PDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 26 publications
0
52
0
5
Order By: Relevance
“…A-PD respite can be an effective temporary solution [31]. In contrast, a 12-month pilot program of assisted PD found that technique survival was not different between self-care and assisted PD patients [31]. However, in that study, the definition of assistance was different, as patients (or their families), were responsible for connecting and disconnecting the cycler and other cycler-related tasks in the assisted program.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A-PD respite can be an effective temporary solution [31]. In contrast, a 12-month pilot program of assisted PD found that technique survival was not different between self-care and assisted PD patients [31]. However, in that study, the definition of assistance was different, as patients (or their families), were responsible for connecting and disconnecting the cycler and other cycler-related tasks in the assisted program.…”
Section: Discussionmentioning
confidence: 69%
“…In elderly Taiwanese patients, those assisted by a home assistant or a family member had the same risk of peritonitis as autonomous PD patients [15]. The results from a pilot program in Canada showed lower rates of peritonitis in the a-PD group compared to the self-care group suggesting that assisted patients may be given responsibility for making their own connections without increasing rates of peritonitis [31]. However, we found that in the older population, nurse assistance was associated with a lower risk of peritonitis [33].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This creation of a "video caregiver" also made it possible not to refer to a family member or professional caregiver, which involves significant social [6] and economic [7,8] costs.…”
Section: Discussionmentioning
confidence: 99%
“…As regards economic costs, the comparison should be made with Assisted PD carried out by a nurse at home [7,8]. Compared to the latter, VD allows for considerable savings associated with the elimination of travelling costs and the fact that up to 6 patients can be followed at the same time instead of just 1.…”
Section: Discussionmentioning
confidence: 99%